Theoretical Studies on One-Photon and Two-Photon Absorption Properties of Platinum Acetylide Complexes (Journal of Atomic and Molecular Sciences, 2018)
The one-photon and two-photon absorption properties of platinum acetylide complexes that feature hightly π-congugated ligands substituted with π-donor or π-acceptor moieties are investigated by use of the analytic response theory at DFT level. The numerical results show that these molecules have relatively strong two-photon absorption activities. While the platium insert into the ligands, TPA cross sections of the metal compounds are significantly enhanced. Metal clusters can also extend the π-conjugated length, which plays an important role in increasing the TPA cross section. Moreover, the NLO properties of metal clusters can be enhanced by the introduction of metal→ligand and ligand→metal charge-transfer states. The charge-transfer process is analyzed when the molecule is excited from the ground state to charge-transfer state.